2016
DOI: 10.1063/1.4944602
|View full text |Cite
|
Sign up to set email alerts
|

Analytical modeling and numerical simulation of the short-wave infrared electron-injection detectors

Abstract: This paper describes comprehensive analytical and simulation models for the design and optimization of the electron-injection based detectors. The electron-injection detectors evaluated here operate in the shortwave infrared range and utilize a type-II band alignment in InP/GaAsSb/ InGaAs material system. The unique geometry of detectors along with an inherent negativefeedback mechanism in the device allows for achieving high internal avalanche-free amplifications without any excess noise. Physics-based closed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Our experimental studies as well as simulation results Movassaghi et al, 2016) demonstrated that in order to achieve very low dark current and fast response time, in a single device, it is necessary to physically separate individual pixels. This results in a pre-defined active area for each detector and allows the charge localization dynamics to be accurately controlled with the active area of each detector.…”
Section: Second-generation Resultsmentioning
confidence: 86%
See 4 more Smart Citations
“…Our experimental studies as well as simulation results Movassaghi et al, 2016) demonstrated that in order to achieve very low dark current and fast response time, in a single device, it is necessary to physically separate individual pixels. This results in a pre-defined active area for each detector and allows the charge localization dynamics to be accurately controlled with the active area of each detector.…”
Section: Second-generation Resultsmentioning
confidence: 86%
“…As shown in Movassaghi et al (2016), the charging rate of the GaAsSb trapping layer by electrons (and the neutralizing holes) is ultimately limited by the minority-electron lifetime in the GaAsSb layer (τe). The ultimate bandwidth of device is thus dictated by the electron lifetime in the GaAsSb layer.…”
Section: Detection Mechanismmentioning
confidence: 99%
See 3 more Smart Citations